Sequential development of ANCA‐associated vasculitis and anti‐GBM disease: A report of two cases. Issue 7 (23rd July 2021) - Le Moine, Camille; Jourde‐Chiche, Noémie; Kemlin, Delphine; Terrier, Benjamin; Vandergheynst, Frédéric
Abstract: In case of AAV with kidney involvement, physicians should explore anti‐GBM antibodies and be aware of the possible sequential development of AAV, especially with MPO‐ANCA, and anti‐GBM glomerulonephritis. This sequential disease history is associated with a poor renal outcome, highlighting the need for urgent diagnosis and management. Abstract : In case of AAV with kidney involvement, physicians should explore anti‐GBM antibodies and be aware of the possible sequential development of AAV, especially with MPO‐ANCA, and anti‐GBM glomerulonephritis. This sequential disease history is associated with a poor renal outcome, highlighting the need for urgent diagnosis and management.